2022
DOI: 10.1186/s12989-022-00476-9
|View full text |Cite
|
Sign up to set email alerts
|

The application of existing genotoxicity methodologies for grouping of nanomaterials: towards an integrated approach to testing and assessment

Abstract: The incorporation of nanomaterials (NMs) in consumer products has proven to be highly valuable in many sectors. Unfortunately, however, the same nano specific physicochemical properties, which make these material attractive, might also contribute to hazards for people exposed to these materials. The physicochemical properties of NMs will impact their interaction with biological surroundings and influence their fate and their potential adverse effects such as genotoxicity. Due to the large and expanding number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The most suitable cell lines for the evaluation of the genotoxicity in nanomaterials have not yet been determined. In addition, a very important knowledge gap in nanogenotoxicity research is that there could be developed in vitro test methods suitable for detecting secondary genotoxicity [ 36 ]. This study showed that in vitro studies could detect the secondary genotoxicity in nanomaterials, especially those mediated by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The most suitable cell lines for the evaluation of the genotoxicity in nanomaterials have not yet been determined. In addition, a very important knowledge gap in nanogenotoxicity research is that there could be developed in vitro test methods suitable for detecting secondary genotoxicity [ 36 ]. This study showed that in vitro studies could detect the secondary genotoxicity in nanomaterials, especially those mediated by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Additionally, possible health hazards of NPs have been manifested by effects on immune defense, T-helper Th1/Th2 balance, and non-immunological aspects such as oxidative stress, apoptosis, autophagy, genotoxicity, and carcinogenesis. 9 , 13 The skin, respiratory and gastrointestinal tracts of the body are connected to the external environment and are therefore the main exposure sites for NPs. 5 Furthermore, NPs have the potential to translocate to different distal organs.…”
Section: Introductionmentioning
confidence: 99%
“…When the initial inhalation hypothesis was developed, insufficient information to support hypothesis generation for genotoxicity of NFs was identified. However, in order to future-proof the Framework, Verdon et al (2022) have generated a genotoxicity tiered testing strategy that can be added into the existing IATA to address this gap, should future hypotheses require consideration of genotoxicity (Figure S1 6 ).…”
mentioning
confidence: 99%